ЕКОНОМІЧНА ЕФЕКТИВНІСТЬ ВИРОБНИЦТВА БІОЧАРУ ТА ТВЕРДОГО ПАЛИВА НА ОС-НОВІ БІОВУГІЛЛЯ - Kramar, V.G.; Kramar, V.G. (Institute of Engineering Thermophysics of NAS of Ukraine, 2024)
Useful disposal of industrial waste and biomass remains is increasingly relevant for Ukrainian enterprises. The purpose of this article is to find additional opportunities for the production of products with greater added value by processing waste and biomass residues to biochar. World prices for biochar are quite high, much higher than for the use of biocoals as fuel, and are around 800 EUR/t, maximum up to 1,800 EUR/t. The main technical characteristics and price offers of equipment for the production of biochar from nine manufacturers from China, Germany, Finland, Norway and the Netherlands were analyzed. The results of feasibility study of the biochar production from sunflower husks on a technological line with an input productivity of 5 t/h for one of the Ukrainian vegetable oils production plants are presented. As the main equipment, a drum-type pyrolyzer heated by synthesis gas, formed during the thermochemical decomposition of biomass, was considered. Byproducts of production are also bioacetic acid and tar oil. The financial indicators in the case of biochar export are attractive enough for implementation. The estimated simple payback period when using granulated husk was about 4 years at a price of biochar of 650 EUR/t and less than one year at a price of 800 EUR/t. When using non-granulated husk, the simple payback period was about 3 years, even at the price of biochar of 450 EUR/t. Possible risks for implementation are the uncertainty regarding market demand and sales opportunities for biochar, quality requirements and the ability of the considered equipment to provide them, insufficient information regarding biochar yield from various biomass, as well as the lack of experience. Enterprises interested in the implementation of such a project are recommended to conduct trial processing of a batch of their raw materials on similar equipment in advance, to determine the share of biochar yield and its quality characteristics, to search for potential buyers to discuss quality requirements and possible prices.